2018
DOI: 10.1186/s12876-018-0859-y
|View full text |Cite
|
Sign up to set email alerts
|

The influence of various distractions prior to upper gastrointestinal endoscopy: a prospective randomized controlled study

Abstract: BackgroundAlthough many patients still have anxiety about upper gastrointestinal (GI) endoscopy, there have been few reports on the influence of distractions for a person who is going to undergo upper GI endoscopy soon. This study was a prospective randomized controlled study investigating the influence of distractions, such as auditive and visual distractions using subjective and objective assessments including autonomic nervous function prior to upper GI endoscopy.Methods206 subjects who underwent upper GI e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
(33 reference statements)
0
16
0
1
Order By: Relevance
“…Hastalardaki ağrı ve anksiyete iyileşmeyi olumsuz etkilemekte ve taburculuğu geciktirebilmektedir (27). Buna karşın, hastaların ağrı ve anksiyetesi etkili biçimde yönetildiğinde kan basıncı, solunum sayısı ve ilaç kullanımının azaldığı, yaşam kalitesinin arttığı ve iyileşme süresinin kısaldığı gözlenmektedir (28,29 Eksizyon işlemi sırasındaki ağrı şiddeti ortalamaları bakımından müdahale ve kontrol grubu arasında istatistiksel anlamlı bir fark vardır (p<0,05) (Tablo-2). İşlem sırasında ağrı şiddeti farkı için etki büyüklüğü (Cohen's d) 0,769, işlem sonrası ağrı şiddeti farkı etki büyüklüğü (Cohen's d) 0,297 olarak hesaplanmıştır.…”
Section: Discussionunclassified
“…Hastalardaki ağrı ve anksiyete iyileşmeyi olumsuz etkilemekte ve taburculuğu geciktirebilmektedir (27). Buna karşın, hastaların ağrı ve anksiyetesi etkili biçimde yönetildiğinde kan basıncı, solunum sayısı ve ilaç kullanımının azaldığı, yaşam kalitesinin arttığı ve iyileşme süresinin kısaldığı gözlenmektedir (28,29 Eksizyon işlemi sırasındaki ağrı şiddeti ortalamaları bakımından müdahale ve kontrol grubu arasında istatistiksel anlamlı bir fark vardır (p<0,05) (Tablo-2). İşlem sırasında ağrı şiddeti farkı için etki büyüklüğü (Cohen's d) 0,769, işlem sonrası ağrı şiddeti farkı etki büyüklüğü (Cohen's d) 0,297 olarak hesaplanmıştır.…”
Section: Discussionunclassified
“…However, it is believed that watching a video can engage both visual and auditory senses. Therefore, it is expected that visual distraction becomes more effective than auditory distraction due to the positive psychological impacts of visual stimulation on patients [30,36].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Lee et al (2004) [ 37 ] showed that audiovisual distraction via a home-made scenic movie with classic music in patients undergoing colonoscopy reduced the dose of medications and the pain score. In the study of Sogabe et al (2018) [ 36 ], patients undergoing upper gastrointestinal endoscopy received visual distraction via watching moving images including mountains, forests, rivers, waterfalls, lakes, sunsets, along with auditive distraction through listening to healing music such as country and classical and a combination of both. It was also shown that their combination was more effective than the use of each one alone.…”
Section: Discussionmentioning
confidence: 99%
“…Previous nursing studies (Ware, 2018) have shown how the degree of satisfaction in digestive endoscopy is linked to nursing skills aimed at reducing anxiety through specific intervention protocols such as the use of visual and auditory distractors (Sogabe et al, 2018). In a similar setting a randomized controlled trial (Cheng-Hua, Wei-Her, TA B L E 3 Variables associated with patients satisfied with the procedure (OUTCOME 1) and willingness to repeat procedure under same conditions (OUTCOME 2) patients undergoing Day Surgery procedures, significantly, benefit from nursing musical intervention to reduce preoperative anxiety and improve physiological parameters.…”
Section: Discussionmentioning
confidence: 99%